2010
DOI: 10.1093/esr/jcp061
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Participation Differentials in Dutch Higher Education: The Impact of Subjective Success Probabilities on Level Choice and Field Choice

Abstract: Nijmegen. His research interests include: consequences of social mobility on ethnic antagonism, the impact of the direct living environment on ethnic antagonism and social cohesion, and educational inequality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 17 publications
(21 reference statements)
4
23
0
1
Order By: Relevance
“…These results suggest that a soft skill (such as recognizing one's own abilities) can have a longlasting impact on educational career. Our findings are consistent with those of Tolsma, Need and de Jong (2010), who found success probability a significant explanatory mechanism in participation in Dutch higher education. Similarly to that finding, we also found significant status differences even after controlling for self-assessment, which suggests that unexplained status differences cannot entirely be attributed to differences in self-assessment.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…These results suggest that a soft skill (such as recognizing one's own abilities) can have a longlasting impact on educational career. Our findings are consistent with those of Tolsma, Need and de Jong (2010), who found success probability a significant explanatory mechanism in participation in Dutch higher education. Similarly to that finding, we also found significant status differences even after controlling for self-assessment, which suggests that unexplained status differences cannot entirely be attributed to differences in self-assessment.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…Filippin and Paccagnella (2011) showed in their model that those who initially overestimate their abilities (a sign of self-confidence) will follow more ambitious educational paths and can accumulate more knowledge than those with low self-confidence, who underestimate their ability. Positive self-assessment (knowledge about own ability) translates into the choice of demanding education at the secondary level (Keller 2014), and perceived probability of success increases the decision to choose to go on to tertiary education (Keller and Neidhöfer 2014;Tolsma, Need, and de Jong 2010).…”
Section: Possible Mechanisms For Why Grades Might Influence School Pementioning
confidence: 99%
“…Students can rely on their knowledge and may be more persuaded of their own abilities. Indeed, it has been found that students with a high social origin are more convinced that they will successfully complete HE (Tolsma, Need, and de Jong 2010). Thus, it may be that students from the lower classes may underestimate their success probabilities.…”
Section: Application Decisions As Mechanisms Of Self-selectionmentioning
confidence: 99%